Orientalism and the Eastern European Periphery - Mihaela Mudure (Linguaculture, 2022)
This paper starts by discussing the specific use of Orientalism in the Romanian culture. Focus is laid upon the Romanian scholar Dimitrie Cantemir (1673-1723), the first Christian historian who was allowed to use the Ottoman archives for his work. Then Ienăchiţă Văcărescu or Kelemen Mikes offer alternative Orientalist discourses. Unfortunately, Said’s seminal essay neglects everything that is East of Vienna in terms of Orientalism. Criticizing the binary opposition West-Orient, in fact Said reiterates it in his work by neglecting the Eastern European periphery. The conclusion is that Central and Eastern Europe (CEE) offers interesting examples of Orientalisms where the power relationships are constructed differently.